Ventricular assist device in a failing total cavopulmonary connection: a new step-by-step approach. (11th September 2017) - Pace Napoleone, Carlo; Cascarano, Maria Teresa; Deorsola, Luca; Valori, Andrea
Abstract: The management of failing Fontan patients with mechanical circulatory support has been reported with unsatisfactory results. A 5-year-old girl, listed for heart transplantation for failing Fontan, underwent rescue extracorporeal membrane oxygenation support. As it was necessary to move the patient to the Berlin Heart Excor, a step-by-step approach was designed to obtain a gradual adaptation to this form of support. A central extracorporeal membrane oxygenation, with a Berlin Heart apical and aortic cannulae, was implanted leaving the previously positioned femoral vein cannula in parallel with the outflow apical one. The femoral vein cannula was removed when the lungs recovered from the effects of surgical trauma. Four days later, the Fontan fenestration was closed, and after 4 more days, a gradual reduction of gas support was planned without problems. Oxygenator was then removed, and 4 days later, a 30-ml Berlin Heart EXCOR ventricle replaced the centrifugal pump. This sequential approach, which has never been described before, can improve the results of the ventricular assist device support in failing Fontan patients, because it allows a gradual adaptation, even in patients with damaged lungs.